Effect of Green Finance, Profitability, Leverage and Company Size on Financial Sustainability Ratio at Sharia Commercial Banks in Indonesia for the Period 2019-2023 - Anggara, Catur Novi; Suripto; M. Iqbal Harori (The Es Accounting And Finance, 2025)
Islamic banking plays an important role in the Indonesian economy by promoting the principles of sustainability and ethics of Islamic finance. However, in the face of global challenges such as climate change and economic uncertainty, Islamic commercial banks need to adopt more effective sustainability strategies to maintain their financial stability. The purpose of this study was to determine the effect of green finance, profitability, leverage and company size on financial sustainability ratio in Sharia commercial banks in Indonesia for the period 2019-2023. Sampling in this study using the method of purpose sampling. The sample included in the criteria are 8 Islamic banking companies. Data analysis technique using multiple linear regression with panel data approach using Eviews 10.0 tool. The results of the partial significance test of the t test in this study is the green finance variable does not significantly affect the financial sustainability ratio. Meanwhile, profitability variables, leverage and company size significantly affect the financial sustainability ratio. The results of the simultaneous significance test F test showed that the variables green finance, profitability, leverage and company size simultaneously significantly affect the financial sustainability ratio. This research contributes to the Islamic banking industry in improving financial sustainability strategies as well as for investors in assessing the financial performance of Islamic commercial banks from a sustainability perspective.